Innovation in Pondok Pesantren Financial Management: Study of the Implementation of a Smart Payment System Based on Virtual Accounts - Ahmad Nurkhin; Abdul Rohman; Tri Jatmiko Wahyu Prabowo; Hasan Mukhibad (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Purpose – Accepting students' syahriyah in Pondok pesantren is vital, so systematic efforts are needed to increase acceptance and manage effectively and efficiently. The purpose of the study was to describe the innovation of Pondok pesantren's financial management that implements smart payments based on virtual accounts. Method – Using interview and documentation data collection techniques, a qualitative descriptive research design was used. The informants in this study were Kiai, financial managers of the boarding school, and treasurers of male and female boarding schools. Validity and reliability tests have been carried out through reliability tests and context dependence tests. Qualitative data analysis techniques, through interactive analysis models, were used as data analysis techniques. Findings – The results of the study showed that the management of the Salaf Pondok pesantren had involved students as full financial managers of the boarding school as a learning medium to carry out the mandate for the good of the boarding school. The financial management of the male and female boarding schools is directly managed by students who have been given the mandate as treasurers. The recapitulation report of expenditures will be submitted periodically to Kiai. The innovation in financial management implemented uses a smart payment system based on virtual accounts to increase the acceptance of Pondok pesantren payments. Another benefit is the speed and accuracy of presenting financial data and information, which has improved. However, there are still payment arrears from students' parents/guardians for various reasons. The smart payment system also controls students' pocket money through smart cards. The responsibility for managing the smart payment system lies with the financial manager of the Salaf Pondok Pesantren, assisted by one student. The receipts of the students' syahriyah are then distributed to the treasurers of the male and female Pesantren. They have further managed to finance the operations of each Pesantren. Kiai receives periodic recapitulation reports of receipts and other financial information if needed. Implications – This study further emphasizes the importance of digitalizing Salaf Pondok pesantren's financial management to accurately and accountably present financial data and information.